Net cleaning impacts Atlantic salmon gill health through microbiome dysbiosis - Elsheshtawy, Ahmed; Clokie, Benjamin Gregory James; Albalat, Amaya; Nylund, Are; Isaksen, Trond Einar; Napsøy Indrebø, Elisabeth; Andersen, Linda; Moore, Lindsey Jane; MacKenzie, Simon (Frontiers in Aquaculture, 2023)
Net biofouling is a crucial obstacle for the global salmon industry in seawater grow-out stage. Current mitigation of net biofouling occurs primarily through the regular removal of biofouling using in situ cleaning. While in situ net cleaning is effective there is uncertainty as to whether the equipment or disposed material has a negative impact upon fish health. The significant surface area and direct contact with the environment leaves the gill and its associated microbiome especially exposed to such concerns. This study aimed to provide a detailed understanding of the impact of in situ net cleaning on Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss) gill health. Three field trials were conducted on commercial farms producing salmon and trout in western Norway. Fouling organisms on net pens and flushed particles during in situ cleaning were identified and screened for major fish pathogens. Hydrographic profile measurements were performed during net cleaning to measure the impact on water quality. Gill samples were collected before and after in situ cleaning and examined for histopathological changes, inflammatory responses and the prevalence of major pathogens. 16S rRNA amplicon sequencing was employed to explore the impact of net cleaning on the gill microbial community. Data obtained identified a diversity of fouling species including hydroids, algae, skeleton shrimps, and filter feeders (bryozoan, blue mussel), a direct impact on measured water quality indicators, a moderate change in gill inflammatory and antigen presentation activity and a large significant change in the gill microbial community. Observed changes in the gill microbiome involve decreased bacterial richness coupled to an increase in identified bacterial genera that are related to negative health consequences. Parallel analyses for pathogen load in biofouling organisms and flushed particles highlighted the presence of several fish bacteria and parasites. However, minor changes were detected in salmon gill pathogen diversity and load. Our results suggest that biofouling organisms may act as transient reservoirs for some fish pathogens but not viruses and the gill microbial dysbiosis could be related to the host stress response to the process of net cleaning and could be indicative of increased mortalities post-cleaning.